Association Between Ambulatory Blood Pressure and Coronary Artery Calcification: The JHS. Issue 6 (26th April 2021) - Zhang, Yiyi; Schwartz, Joseph E.; Jaeger, Byron C.; An, Jaejin; Bellows, Brandon K.; Clark, Donald; Langford, Aisha T.; Kalinowski, Jolaade; Ogedegbe, Olugbenga; Carr, John Jeffrey; Terry, James G.; Min, Yuan-I.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : High blood pressure (BP) based on measurements obtained in the office setting has been associated with the presence and level of coronary artery calcification (CAC)—a measure of subclinical atherosclerosis. We studied the association between out-of-office BP and CAC among 557 participants who underwent 24-hour ambulatory BP monitoring at visit 1 in 2000–2004 and a computed tomography scan at visit 2 in 2005–2008 as part of the JHS (Jackson Heart Study)—a community-based cohort of African American adults. Mean awake, asleep, and 24-hour BP were calculated for each participant. Among participants included in this analysis, 279 (50%) had any CAC defined by an Agatston score >0. After multivariable adjustment including office systolic BP (SBP), the prevalence ratios for any CAC comparing the highest versus the lowest quartiles of SBP on ambulatory BP monitoring were 1.08 (95% CI, 0.84–1.39) for awake SBP, 1.32 (95% CI, 1.01–1.74) for asleep SBP, and 1.19 (95% CI, 0.91–1.55) for 24-hour SBP. After multivariable adjustment including office diastolic BP, the prevalence ratios for any CAC comparing the highest versus the lowest quartiles of awake, asleep, and 24-hour diastolic BP were 1.27 (95% CI, 1.02–1.59), 1.29 (95% CI, 1.02–1.64), and 1.25 (95% CI, 0.99–1.59), respectively. The current results suggest that higher asleep SBP and higher awake and asleep diastolic BP may be risk factors for subclinical atherosclerosis and underscore the potential role of ambulatory BP monitoring in identifying individuals at high risk for coronary artery disease.